The JWST Early Release Science Program for the Direct Imaging and Spectroscopy of Exoplanetary Systems. (1st September 2022) - Hinkley, Sasha; Carter, Aarynn L.; Ray, Shrishmoy; Skemer, Andrew; Biller, Beth; Choquet, Elodie; Millar-Blanchaer, Maxwell A.; Sallum, Stephanie; Miles, Brittany; Whiteford, Niall; Patapis, Polychronis; Perrin, Marshall; et al.
Abstract: The direct characterization of exoplanetary systems with high-contrast imaging is among the highest priorities for the broader exoplanet community. As large space missions will be necessary for detecting and characterizing exo-Earth twins, developing the techniques and technology for direct imaging of exoplanets is a driving focus for the community. For the first time, JWST will directly observe extrasolar planets at mid-infrared wavelengths beyond 5 μ m, deliver detailed spectroscopy revealing much more precise chemical abundances and atmospheric conditions, and provide sensitivity to analogs of our solar system ice-giant planets at wide orbital separations, an entirely new class of exoplanet. However, in order to maximize the scientific output over the lifetime of the mission, an exquisite understanding of the instrumental performance of JWST is needed as early in the mission as possible. In this paper, we describe our 55 hr Early Release Science Program that will utilize all four JWST instruments to extend the characterization of planetary-mass companions to ∼15 μ m as well as image a circumstellar disk in the mid-infrared with unprecedented sensitivity. Our program will also assess the performance of the observatory in the key modes expected to be commonly used for exoplanet direct imaging and spectroscopy, optimize data calibration and processing, and generate representative data sets that will enable a broad user base to effectively plan for general observing programs in future Cycles.